Circumventing Protocol and Building Collaborative Histories: A Conversation on Freedom Tours with Tania Willard, Cheryl L’Hirondelle, and Camille Turner - Phillips-Amos, Georgia; Hornstein, Stéphanie (RACAR : Revue d'art canadienne / Canadian Art Review, 2025)
In 2017, artists Cheryl L’Hirondelle and Camille Turner collaborated to stage Freedom Tours, two performative interventions in Canadian National Parks. The work was commissioned by Partners in Art for LandMarks2017/Repères2017, a nationwide public arts project across twenty national parks, featuring seven curators and twelve artists. The occasion was the 150th anniversary of Canadian confederation, though, as the LandMarks curators made clear, “a hundred and fifty years is not a long time,” if you consider that there are “marked mammoth bones […which] suggest that the first humans inhabited Turtle Island over 28,000 years ago.”Freedom Tours took the form of two participatory interventions emphasizing Haudenosaunee, Anishinaabe, and Black histories in the territory: a guided boat tour at Thousand Islands National Parks and an intergenerational walking tour or procession at Rouge National Urban Park. In 2024, we met with curator Tania Willard and artists Cheryl L’Hirondelle and Camille Turner over zoom to discuss the frictions and the sparks that arose from this project. What follows is a distilled version of that conversation.